Effect of irradiation dose and shelf life on microbial count in Asam Keumamah - Abdul Hadi; Andriani Andriani; Wiqayatun Khazanah; Husna Husna; Ampera Miko (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Ready-to-eat foods are required immediately in disaster situations. Asam Keumamah is a ready-to-eat product that is not durable. Irradiation with asam keumamah extends the shelf life of the product, reduces microbial load, and maintains nutrition. This study aimed to determine the microbiological quality and food safety of Asam Keumamah irradiated at different doses. The experimental research used a Factorial Completely Randomized Design (CRD) on Asam Keumamah samples that had been irradiated at doses of 0, 20, 30, 40, and 50 kGy and stored for 0, 1, 3, and 6 months at room temperature. The irradiation of Asam Keumamah was carried out at the Merah Putih Gamma Irradiator Merah Putih in the Puspitek area, Serpong, South Tangerang. The total bacterial test on all samples using TPC was conducted at the Balai Perikanan Budidaya Air Payau Ujung Bate (BPBAP-UB) Aceh Besar Laboratory. Data were analyzed using factorial Anova test and Duncan’s test at 95% CI. The results showed that the irradiation dose had a significant effect on the number of bacteria (p<0,05), the storage period had no significant effect on the number of bacteria (p>0,05), and the interaction between irradiation dose and storage period had a significant effect on the number of Asam Keumamah bacteria (p=0,0001). This study concluded that the higher the irradiation dose, the lower the number of bacteria and durability.